Pembuatan Lubang Resapan Biopori Dalam Upaya Konservasi Air Tanah Di Dalam Pekarangan Rumah - Devi Eka Lestari; Tugiyono; Gregorius Nugroho Susanto; Elly Lestari (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Banjar Agung Udik village is an area in Pugung Sub-District, Tanggamus Regency, which is located close to Mount Tanggamus. This activity aims to provide training on making biopore infiltration holes in an effort to conserve groundwater in the yard, with the aim of increasing the absorption of rainwater into the soil. This training is expected to reduce the risk of flooding due to rainwater and increase the amount of clean water reserves in the soil. This activity was held on August 6, 2024, at the Banjar Agung Udik village hall, with participants from various age groups, both men and women. The activity began with problem analysis through field surveys, followed by the preparation of an activity plan, training implementation, and ended with socialization and guidance on making biopore infiltration holes in an effort to conserve groundwater in home yards. With continuous training, it is expected that participants will gain knowledge and skills that can be used to reduce the risk of flooding due to overflowing rainwater and to increase the amount of clean water reserves in the soil.